Advanced psychiatric nurse practitioners’ ideas and needs for supervision in private practice in South Africa - Annie M. Temane; Marie Poggenpoel; Chris P.H. Myburgh (Curationis, 2014)
Background: Supervision forms an integral part of psychiatric nursing. The value of clinicalsupervision has been demonstrated widely in research. Despite efforts made toward advancedpsychiatric nursing, supervision seems to be non-existent in this field. Objectives: The aim of this study was to explore and describe advanced psychiatric nursepractitioners’ ideas and needs with regard to supervision in private practice in order tocontribute to the new efforts made in advanced psychiatric nursing in South Africa. Method: A qualitative, descriptive, exploratory, and contextual design using a phenomenological approach as research method was utilised in this study. A purposive sampling was used. Eight advanced psychiatric nurse practitioners in private practice described their ideas and needs for supervision during phenomenological interviews. Tesch’s method of open coding was utilised to analyse data. After data analysis the findings were recontextualised within literature. Results: The data analysis generated the following themes – that the supervisor should have or possess: (a) professional competencies, (b) personal competencies and (c) specificfacilitative communication skills. The findings indicated that there was a need for supervision of advanced psychiatric nurse practitioners in private practice in South Africa. Conclusion: This study indicates that there is need for supervision and competent supervisors in private practice. Supervision can be beneficial with regard to developing a culture of support for advanced psychiatric practitioners in private practice and also psychiatric nurse practitioners.